Do fund size and flows matter? Investigating the determinants of the performance of Philippine peso equity unit investment trust funds (UITFs) - Huang, Trisha T. (Animo Repository, 2022)
Often seen as an accessible means of passive investment, equity funds have been growing in popularity around the world. To distinguish among the thousands of funds globally, investors rely on published information on fund attributes; thus, having a better understanding about how these attributes relate to performance would be useful in making informed decisions. However, existing studies use performance measures insufficiently adjusted for risk or fail to account for important attributes. Hence, we measure fund performance using the Jensen index, the information ratio, and variations of the Treynor measure (the T2 index and the generalized Treynor measure), which we compute using estimates from the single-factor model, the Fama-French three-factor model, and the Fama-French five-factor model. Using quarterly Philippine peso equity Unit Investment Trust Fund (UITF) data from 2010 to 2019, we examine the relationships between fund performance and fund size and flows using the random effects (RE) and pooled ordinary least squares (OLS) estimation techniques with cluster-robust standard errors while considering the potential influences of other fund attributes as well. We find that fund size is relevant for investors seeking to add Philippine equity UITFs to their set of actively managed sub-portfolios while there is no evidence of a relationship between fund flows and performance.